Pengaruh quality of work life dan motivasi intrinsik terhadap kinerja perawat rsud a.m. parikesit tenggarong seberang - Arinda, Puri; Pongtuluran, Yonathan; Lestari AS, Dirga (KINERJA, 2016)
The purpose of this study was to determine the influence of Quality of Work Life and Motivation Intrinsic on Employee Performance. This research was conducted at the Hospital A.M. Parikesit Tenggarong Seberang. The sample of this study consists of 62 respondent. Sampling method using simple random sampling. The data in this study using primary data, interviews and questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS for Windows Version 21. The results of this study show that: 1) Quality of work life has a positive and significant effect on employee performance at the Hospital A.M. Parikesit Tenggarong Seberang, 2) Motivation intrinsic has a positive and significant effect on employee performance at the Hospital A.M. Parikesit Tenggarong Seberang. Keywords: Employee Performance, Quality of Work Life, Motivation Intrinsic.